The impact of multidimensional excessive social media use on academic performance: the moderating role of mindfulness - Ma, Xu; Liu, Qi; Zhang, Wen (Frontiers in Psychology, 2025)
IntroductionThis study investigates the negative impact of excessive social media use among college students on learning burnout and academic performance, categorizing excessive use into three types: excessive social, excessive hedonic, and excessive cognitive. Based on the SSO (Stressor-Strain-Outcome) framework, the research examines the effects of these three types of excessive use on learning burnout and academic performance. It further explores the mediating role of learning burnout and the moderating effects of mindfulness in mitigating these negative outcomes.MethodA total of 532 valid responses were collected via an online survey using standardized self-report measures to assess excessive social media use, learning burnout, academic performance, and mindfulness. Data were analyzed using SPSS 26.0 for descriptive statistics and moderation analysis, while AMOS 26.0 was employed for structural equation modeling and mediation testing.ResultsExcessive social and hedonic use significantly increased learning burnout, while excessive cognitive use reduced it. Learning burnout negatively impacted academic performance and mediated the effects of all three types of social media use. Mindfulness moderated these relationships, weakening the adverse effects of excessive social media use.DiscussionThe study reveals distinct effects of different types of excessive social media use on learning burnout and academic performance, underscoring the protective role of mindfulness. These findings offer valuable insights for developing interventions to enhance academic performance among college students.